Association of R47H variant in the TREM2 gene and genetics susceptibility to Alzheimer’s disease in Serbian population: Analysis of the frequency of the R47H variant in the TREM2 gene among patients with Alzheimer’s disease - Andrejić, Nikola (Medical Research, 2023)
Introduction: Alzheimer's disease (AD) is a chronic neurodegenerative disease, which is clinically manifested by the development of dementia. Studies of genetic susceptibility to AD indicate a whole range of genes and their variants that can potentially influence an individual's susceptibility to develop the disease. AD17 represents a form of Alzheimer's disease associated with mutation(s) in the TREM2 gene, encoding triggering receptor expressed on myeloid cells 2. The aim of this study was to determine the frequency of R47H variant of the TREM2 gene in the population of AD patients, to compare the frequency of the variant in the population of AD patients and the control group, and to determine the possible association of a certain genotype with the susceptibility to develop the disease.                            Material and Methods: Study included 168 consecutive patients with AD and 190 healthy controls. The clinical inerview, neurologic examination, and neuropsychological set of cognitive assesment was performed by neurologists and neuropsychologists in expertise with neurodegenerative deseases. Genotyping of rs75932628, R47H polymorphism of the TREM2 gene was performed using Real-time Polymerase Chain Reaction and TaqMan® SNP genotyping assay (Applied Biosystem by Thermo Fisher Scientific, USA) according to the recommendation of the manufacturer. Results: In the group of AD patients the frequency of C allele was 98.8%, while the T allele was present in 1.2% of patients. The frequency of the T allele was statistically significantly higher among the AD population than among the control group (p
Keywords: Alzheimer's disease; polymorphism; prevalence; TREM2; R47H